2017
DOI: 10.3899/jrheum.170046
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Treatment, Outcomes, and Incidence of Orthopedic Surgery in Patients with Rheumatoid Arthritis: An Observational Cohort Study Using the Japanese National Database of Rheumatic Diseases

Abstract: The overall incidence of orthopedic surgeries in patients with RA significantly decreased, accompanied by improved clinical outcomes because of the expanded use of effective drugs; however, the declining trend differed between procedures or locations. The results from the present study suggest that there might be a change in supply and demand for orthopedic surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 36 publications
2
22
0
1
Order By: Relevance
“…Our results were in conformity with other international studies that showed the reduction in surgical treatment indications. [11][12][13] In a Norwegian population, 13 a study conducted in 6394 RA patients between 1994 and 2012 showed that the incidence of arthroplasties decreased from 7.5 p/100,000 person-year in 1997 to 0.5/100,000 person-year in 2012. Concerning synovectomy and arthrodesis, their rate decreased from 5.4 and 10.3/100,000 person-year in 1997 to 1.1 and 5.7/100,000 person-year in 2012, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results were in conformity with other international studies that showed the reduction in surgical treatment indications. [11][12][13] In a Norwegian population, 13 a study conducted in 6394 RA patients between 1994 and 2012 showed that the incidence of arthroplasties decreased from 7.5 p/100,000 person-year in 1997 to 0.5/100,000 person-year in 2012. Concerning synovectomy and arthrodesis, their rate decreased from 5.4 and 10.3/100,000 person-year in 1997 to 1.1 and 5.7/100,000 person-year in 2012, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning synovectomy and arthrodesis, their rate decreased from 5.4 and 10.3/100,000 person-year in 1997 to 1.1 and 5.7/100,000 person-year in 2012, respectively. Moreover, in Japanese patients with RA, 12 total number of surgical treatment decreased from 72/1,000 in 2004 to 51.5/1,000 in 2014 with a reduction from 11.5/1,000 to 6.1/1,000 for total hip replacement and from 30.1/1,000 to 8.51/1,000 for total knee replacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of two cohorts of RA patients from the 1980s and 1990s, 20%‐30% of patients became unable to work within three to four years of diagnosis . Disease activity levels and disability have fallen in the last 15 years with more intensive treatment . Despite the advances in therapy, RA is a chronic disease where most patients need some form of DMARD therapy indefinitely.…”
Section: Clinical Features and Epidemiology Of Ra Spa And Ici‐iamentioning
confidence: 99%
“…and disability have fallen in the last 15 years with more intensive treatment. 48,49 Despite the advances in therapy, RA is a chronic disease where most patients need some form of DMARD therapy indefinitely.…”
Section: Common To Have Disability In 2-3 Y If Untreatedmentioning
confidence: 99%